Respuesta :

Step-by-step explanation:  

x²+ y² -12x - 18y +17 = 0 means : (x²-12x+36)-36+(y²-18y+81)-81-27 =0

(x-6)²+(y-9)² =12²....standard form when the center is (-6 , 9) and radius 12

Answer:

The center is at (1, 6) and the radius is 1.

Step-by-step explanation:

x^2 + y^2 - 2x - 12y +36 = 0

Convert to standard form:

x^2 - 2x + y^2 - 12y = -36

(x - 1)^2 - 1 + (y - 6)^2 - 36 = -36

(x - 1)^2 + (y - 6)^2 = -36 + 36 + 1

(x - 1)^2 + (y - 6)^2 =  1

The center is at (1, 6) and the radius is 1.